Applying the concept of diversity management in organisations in the Czech Republic and the Slovak Republic – a research survey - Egerova, Dana; Jiřincova, Milena; Lančarič, Drahoslav; Savov, Radovan (Technological and Economic Development of Economy, 2013)
The paper deals with the implementation of diversity management in the Czech and Slovak organizations. The aim of the research was to find out how the concept of diversity management is accepted and applied in the Czech and Slovak companies. The scale questionnaire of the author’s own construction was used for data collection. The questionnaire contained apart from the introductory classification items 25 items divided into three thematic areas: the field of inclusion and justice, the field of diversity management implementation and the field of benefits resulting from implementing diversity management. The statistically significant differences and dependencies that emerged among items in the questionnaire were examined by Kruskal-Wallis test and other statistical methods. The research survey revealed that respondents’ answers were significantly affected by factors such as the seat of the company and the working position of the respondent. The respondents from the Slovak Republic generally perceive issue of diversity management more positively compared with respondents from the Czech Republic. Also the managers perceive issue of diversity management more positively compared with employees. The research survey identified partially the existing state of implementing the concept of diversity management in organizations in the Czech and Slovak Republics.